2019
DOI: 10.1111/jam.14501
|View full text |Cite
|
Sign up to set email alerts
|

Investigation ofStreptococcus agalactiaeusingpcsB‐based LAMP in milk, tilapia and vaginal swabs in Haikou, China

Abstract: Aims To develop a pcsB‐based Loop‐mediated isothermal amplification (LAMP) method for the detection of Streptococcus agalactiae (GBS) in milk, tilapia and vaginal swabs. Methods and Results The sensitivity of the LAMP method using real‐time turbidity monitoring was 1 pg of template within 1 h at 64°C, 100‐fold higher than conventional PCR. The sensitivity of visual detection dropped an order of magnitude using SYBR Green I or hydroxynaphthol blue. The validity of the visual LAMP assay was assessed by the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…The minimum detection limit of the S. agalactiae -MCDA-LFB assay is 300 fg, which is 333-fold more sensitive than the S. agalactiae -PCR assay, the detection threshold of which was 100 pg ( Pu et al, 2019 ). Apart from its excellent sensitivity, the MCDA-LFB assay also has high specificity that can clearly differentiate S. agalactiae from other Streptococcus and non- Streptococcus species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The minimum detection limit of the S. agalactiae -MCDA-LFB assay is 300 fg, which is 333-fold more sensitive than the S. agalactiae -PCR assay, the detection threshold of which was 100 pg ( Pu et al, 2019 ). Apart from its excellent sensitivity, the MCDA-LFB assay also has high specificity that can clearly differentiate S. agalactiae from other Streptococcus and non- Streptococcus species.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the sensitivity of qPCR is controversial, as it varied from 62.5 to 98.5% compared to that of the bacterial culture method ( Verani et al, 2010 ). The popular loop-mediated isothermal amplification (LAMP) assay has also been developed for detecting S. agalactiae ( Kimura et al, 2013 ; Pu et al, 2019 ), and the LAMP products were usually analyzed by a turbidimeter or colorimetric indicator. However, the results obtained by a turbidimeter inevitably suffer from background interference, and the results are somewhat subjective when using colorimetric indicator with the naked eye, especially when using a limited quantity of DNA, usually leading to false-negative results.…”
Section: Introductionmentioning
confidence: 99%
“…The whole experiment only depends on a simple heater, with the weight of 1 kg, which is very easy to achieve in resource-limited restricts, not like an expensive thermal cycler that required for qPCR. The detection limit of the MCDA assay was 250 fg, which is more sensitive than 100 pg of PCR and 1 pg of LAMP (Pu et al 2019). The MCDA assay depends on ten specific primers recognizing 10 different regions of pcsB sequence to accomplish amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Garg et al [ 40 ] introduced successful LAMP-based turbidimetric detection of Mycobacterium leprae targeting the 16s rRNA gene. Likewise, similar studies reported the detection of multiple pathogens—for instance, Clostridium botulinum [ 41 ], Streptococcus pneumoniae [ 42 ], and Streptococcus agalactiae [ 43 ]. However, this method provides low sensitivity, as the faint product can easily be misjudged.…”
Section: Lamp Detection Methodsmentioning
confidence: 99%